Memory spaces and linguistic substrates from the backstrap loom in the Sierra Liberteña - Quiroz Malca, Haydée (2021)
This article presents preliminary advances from a survey of the backstrap loom´s components names, currently in use in three highlands provinces of La Libertad: Otuzco, Santiago de Chuco and Sánchez Carrión; part of the consensual area of the culle language, belonging to the colonial bishopric of Trujillo. It begins with a brief discussion on the role of textiles in the Andean world, and the analytical categories such as discontinuous territorialities and cultural configurations, which allow us to understand the processes of textile production in this area. Added to a brief socio-demographic description of the region and provinces of study. It was proposed to use the names of the instruments of the waist loom or kallwa as a methodological tool, to broaden the understanding of ethnic presences, as well as the exchanges, not only of products but also of technical knowledge associated with population movements. The findings of culle and quechua substrates are presented, and a comparison with provinces of the neighboring department of Cajamarca, from which presences and disagreements are inferred that could show knowledge and cults shared in a wider región.